2023
DOI: 10.1111/gcb.17097
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of water conditions in the responses of autumn phenology of marsh wetlands to climate change on the Tibetan Plateau

Xiangjin Shen,
Miaogen Shen,
Chaoyang Wu
et al.

Abstract: The Tibetan Plateau, housing 20% of China's wetlands, plays a vital role in the regional carbon cycle. Examining the phenological dynamics of wetland vegetation in response to climate change is crucial for understanding its impact on the ecosystem. Despite this importance, the specific effects of climate change on wetland vegetation phenology in this region remain uncertain. In this study, we investigated the influence of climate change on the end of the growing season (EOS) of marsh wetland vegetation across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…The compensatory effect is a phenomenon that vegetation produces more organic matter the next day after consuming organic matter due to nighttime warming, resulting in some recovery of vegetation growth ( Peng et al., 2013 ; Ulrich et al., 2019 ). Previous studies have shown that environments with sufficient water easily lead to a compensatory effect and even a super compensatory effect ( Liu et al., 2023b ; Shen et al., 2024 ), which can recover and even exceed the original state of the vegetation ( Wang et al., 2023 ; Liu et al., 2023a ). The subject of this study was marsh wetland with sufficient water and nutrients ( Shen et al., 2022b ); therefore, a super compensatory effect may have occurred in this region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The compensatory effect is a phenomenon that vegetation produces more organic matter the next day after consuming organic matter due to nighttime warming, resulting in some recovery of vegetation growth ( Peng et al., 2013 ; Ulrich et al., 2019 ). Previous studies have shown that environments with sufficient water easily lead to a compensatory effect and even a super compensatory effect ( Liu et al., 2023b ; Shen et al., 2024 ), which can recover and even exceed the original state of the vegetation ( Wang et al., 2023 ; Liu et al., 2023a ). The subject of this study was marsh wetland with sufficient water and nutrients ( Shen et al., 2022b ); therefore, a super compensatory effect may have occurred in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The environment of TAS are more arid, and precipitation is the limiting factor for the growth of vegetation in this region ( Wang et al., 2023 ). Increased spring precipitation can effectively alleviate the drought stress suffered by the vegetation, and is beneficial to the growth of the vegetation ( Abel et al., 2023 ; Zhu et al., 2023 ; Shen et al., 2024 ). This could explain why the increase in spring precipitation leads to an increase in NPP in the temperate semi-arid and arid marsh regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics of remote sensing data compensate for the shortcomings of traditional vegetation phenology observation methods, rendering them extensively applied in regional and worldwide vegetation phenology research [ 3 , 4 , 12 ]. The Normalized Difference Vegetation Index (NDVI) has been extensively utilized in quantitative research of vegetation phenology due to its robustness and simplicity [ 13 , 14 , 15 ]. According to the majority of previous vegetation phenology studies based on satellite data, the SOS advanced owing to global warming [ 16 ].…”
Section: Introductionmentioning
confidence: 99%